KESETIMBANGAN PROSES DESORPSI AMONIA DARI ARANG AKTIF HASIL PIROLISIS LIMBAH BIOMASSA - Hasni Hasni; Syamsuddin Yani; Andi Aladin; Mimin Septiani (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2020)
Ammonia which is bound to the adsorbent can interfere adsorption process, so that release the compound can be done by desorption process. This research intends to know appropriate equilibrium models to determine maximum capacity of active carbon for desorption ammonia. The method which used in desorption process are Langmuir and Freundlich isotherm models. The research was performed with variation of active carbon mass and variation of contact time. The concentration of ammonia on the desorption process was determined using spectrophotometer at λ 420 nm. The experiment result showed that the more the active carbon dosage is used, the more the concentration of ammonia is increased. Optimum contact time during 7 hours with desorption percentage 94-96%. This research of ammonia desorption by active carbon followed the Langmuir equilibrium model R2 0.954 and Freundlich equilibrium model R2 0.952. The equilibrium equation is used Langmuir equation y = -0.015x + 3.185, maximum desorption capacity is 66.67 mg/g.